Polyvinyl alcohol surface modification - Thomas, M; Matthew Thomas (2011)
Poly(vinyl alcohol) (PVA) is a polymer used in numerous applications, principally those in which its high water solubility is a desirable asset. However there are also areas where PVA is limited by its inherent solubility (for example some specific environments in the biomedical field). This work has sought to overcome such limits by manipulating the surface of PVA in order to propose various means by which the surface solvent resistance might be increased while maintaining the bulk properties of the polymer. Both chemical and physical modifications have been tried and in each case progress has been made towards insolubilizing a single surface of the polymer when in film form. Grafting various species onto the surface of PVA was successfully performed. It is believed that such species bonded to the PVA via attachment to the hydroxyl groups (though this has not been proven conclusively). The data contained herein has led to the conclusion that the primary factor in reducing solubility this way is the removal of the hydroxyl groups, and not the attachment of specifically highly hydrophobic molecules. Introducing permanent cross-links into the surface region has been attempted via various routes. The data recorded shows promise however the system is far from optimised. The biggest challenge remaining is to optimise the depth of material cross-linked. Some steps have been made towards understanding and controlling this parameter though there is much scope for further investigation. The methods used have built on those used for bulk cross-linking and as such are new for the case of surface specific treatment. An interesting phenomenon in some semi-crystalline polymers reported in recent years is that of surface specific crystallization. This effect has been successfully induced and observed in PVA to produce what is believed to be a highly crystalline surface layer, and crystalline regions of PVA are generally accepted to be more water resistant than amorphous ones. In summary, in this work several surface-specific treatments for PVA have been trialled, providing options for post-film forming modification to reduce the surface water sensitivity whilst retaining the bulk properties of the polymer.